2008
DOI: 10.1590/s0037-86822008000200007
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomicose no Hospital Universitário de Brasília

Abstract: RESUMOForam estudados 76 pacientes com paracoccidioidomicose, assistidos no Hospital Universitário de Brasília, entre 1984 e 2005. O gênero masculino representou 82,9% e a média de idade foi 42 anos. Atividades agropecuárias caracterizaram 54,9% dos pacientes. Entre pacientes com a forma crônica, 87% eram tabagistas e 55,3% etilistas. Em 71 pacientes sem co-infecção por HIV/aids: a) houve recidiva da paracoccidioidomicose em 21 (29,6%); b) a forma crônica ou mista acometeu 77,5% dos pacientes, com predominânci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
11
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
7
11
3
1
Order By: Relevance
“…The predominance of male patients is consistent with findings from studies that found male-to-female ratios between 5:1 to 16.3:1 in Mato Grosso do Sul, Brasília, São Paulo and Rio Grande do Sul (Londero and Ramos, 1990; Blotta et al , 1999; Paniago et al , 2003; Shikanai-Yasuda et al , 2006; Campos et al , 2008). This difference may be explained by a hormone protective factor in women.…”
Section: Discussionsupporting
confidence: 89%
“…The predominance of male patients is consistent with findings from studies that found male-to-female ratios between 5:1 to 16.3:1 in Mato Grosso do Sul, Brasília, São Paulo and Rio Grande do Sul (Londero and Ramos, 1990; Blotta et al , 1999; Paniago et al , 2003; Shikanai-Yasuda et al , 2006; Campos et al , 2008). This difference may be explained by a hormone protective factor in women.…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of acute/subacute cases in our series was similar to that referenced in other publications 3,12,19,20 and the main signs and symptoms had similar frequencies to those observed in other series. 14,17,21,22 Skin lesions were found at a higher frequency in our population than in other series. 14,17 These lesions arouse a high degree of disease suspicion, and because they offered easy access to direct examination and biopsy, they significantly contributed to the diagnosis.…”
Section: Discussioncontrasting
confidence: 51%
“…9 Alcohol use was reported by 57.5% of the 341 patients surveyed, a proportion close to the 55.3% reported at Hospital Universitário de Brasília. 17 In addition to the effects of alcohol on a patient's immune response , 18 the lack of compliance to treatment by alcoholic patients was also noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the predominance of NPCM in men was 13/1, and is in accordance with previous reports 7,11,20,[29][30][31] . In some studies, NPCM occurred exclusively in men 10,32 .…”
Section: Discussionsupporting
confidence: 93%
“…Soil is the main natural source for infectious airborne conidia and people living in rural areas are the main population at risk 8 . In this study, occupational activity related to soil was present in 58% of cases, in accordance with previous reports 10,20,[30][31][32]35,36 although this information could be underestimated due to lack of appropriate investigation during anamnesis. Occasional non-autochthonous cases of PCM have been reported outside Latin America 37 .…”
Section: Discussionsupporting
confidence: 92%